The political potential of logophagy in Rogelio López Cuenca’s work - Gallego Benot, Juan (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper begins by considering those artistic processes described as «logophagyc» by Professor Túa Blesa (1998; 2011). Logophagy’s theoretical roots are hence described as well as its typology, by linking it to Jacques Derrida’s philosophical project and specifically to his work Plato’s Pharmacy. The viability of analysing some of Rogelio Lopez Cuenca’s works in the light of these theories is then studied; special attention is taken to those works which are conveyed through a challenging of writing techniques and its political implications. It is finally shown how the «silence» of logophagy’s techniques has both political roots and expressions in the visual artist’s works.